Combination of Five Body Positions Can Effectively Improve the Rate of Gastric Mucosa’s Complete Visualization by Applying Magnetic-Guided Capsule Endoscopy - Yuting Qian; Sheng Wu; Qi Wang; Lumin Wei; Wei Wu; Lifu Wang; Ye Chu (Gastroenterology Research and Practice)
Objectives. Achieving a comprehensive view of gastric mucosa has been a challenge for magnetic-guided capsule endoscopy (MGCE) for years. This study works on optimizing the performance of MGCE by changing the conventional positions to the five body positions. Methods. Sixty patients were enrolled in the study and underwent MGCE. All patients were asked to adopt five body positions (left lateral, supine, right lateral, knee-chest, and sitting). In each position, the ability to visualize the six gastric landmarks (cardia, fundus, body, angulus, antrum, and pylorus) was assessed. Rates of complete visualization were calculated for different position combinations. Results. Supine position was the best for cardia and body visualization (91.7% and 86.7%, resp., p<0.001). Left lateral position was the best for fundus visualization (91.7%, p<0.001). Knee-chest position was the best for angulus observation (80.0%, p<0.001). Right lateral and sitting positions were the best for antrum observation (88.3% and 90.0%, resp., p<0.001). Right lateral position was the best for pylorus observation (81.7%, p<0.001). The supine + right lateral + knee-chest combination achieved better angulus visualization than conventional 3-position combination (93.3% versus 63.3%, p<0.001). Five-position combination significantly improved the comprehensive gastric landmark visualization (93.3%, p<0.001). Conclusion. Compared with 3-position combination, 5-position combination should be adopted for gastric mucosal visualization by MGCE.